A Delayed and Rather Unusual Presentation of a Bladder Injury after Pelvic Trauma: 5 Years after a Road Traffic Accident - Nikolaos Davarinos; John Thornhill; JP McElwain; David Moore (Case Reports in Orthopedics)
Associated injuries frequently occur in patients who sustain fractures of the pelvis. Specifically, high-energy trauma resulting in pelvic fractures places the bladder and urethra at risk for injury, often resulting in significant complications. Timely identification and management of genitourinary injuries minimize associated morbidity. Prompt injury identification depends upon a systematic evaluation with careful consideration of the mechanism of injury. Physical examination is pertinent as well as analysis of the urine and appropriate diagnostic imaging. Despite such increased vigilance genitourinary injuries get missed and delayed presentations in the order of a few weeks have been well documented. To our knowledge, this is the first report of its kind in the literature showing such a particularly delayed (5 years) and rather unusual presentation of a bladder injury after pelvic trauma.